Brain drain and tax competition: Do we need another BEPS? - Milogolov Nikolai; Berberov Azamat (Anali Pravnog Fakulteta u Beogradu)
In the article we argue that the origins of the international tax base erosion in the corporate sector, which are the harmful tax competition for capital and old-fashioned international tax rules, are also relevant for the taxation of income of the high-skilled and mobile workforce. Therefore, a multilateral rethinking of the global tax architecture is proposed in order to conceptually address the problem properly and in a harmonized manner. We point out, based on the examples of Russia and Serbia, several problems of tax base erosion for mobile "talents", with a case study analysis of scenarios of "talent" migration involving sportspersons, researchers and IT specialists. Finally, we propose some ideas for global tax cooperation in order to mitigate the negative tax effects of brain drain based on adapting the existing recommendations of the BEPS Project for the cases of migrating individuals.